Supplementation of Polyherbal Antistressor Premix as Heat Ameliorating and Immunomodulatory Agent in Broilers during Summer Stress - Keregallikoppalu, Hemanth Gowda; Puttaswamy, Chethan Kenchammana; H S, Shwetha; Puttamallappa, Ravikumar; Jagadeeswary, Vankayala; Miranda, Cherryl D (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted in broiler chickens to evaluate the effect of supplementation of polyherbal antistressor products on heat ameliorating activity and immunomodulatory properties. In the current study a total 90, day old broiler chicks were selected and randomly assigned into three groups on the basis of body weight with two replicates consisting of 15 chicks in each replicate and 30 chicks in each group. Group T0was control group whereas T1 and T2 were treatment groups. Group T1 was fed Ayucee premix supplement @ 100 g/tonne for 0-42 days, Group T2was fed Stresomix Premix @ 250g/tonne for 0-42 days. The growth performance was recorded on day 7, 14, 21, 28, 35 and 42 of age. Blood samples were collected on 5th week from 6 representative birds of each replicate. The haemoglobin, PCV, H/L count, TLC, cortisol, immune organ weight, blood glucose, BUN, serum cholesterol, ALP, AST, and LDH were estimated. The individual vital organ weight of liver, spleen, kidney, thymus and bursa were noted. During fifth and sixth week of age, the T2 group showed significantly (p<0.05) higher body weight and higher level of Hb and PCV than other groups. The weights of spleen, bursa and thymus, antibody titer against ND, activities of SOD, CAT, and GPx were significantly higher in T1 and T2 supplemented groups compared to control group. The results suggested that the polyherbal antistressors supplementation in diet was helpful to ameliorate heat stress in broilers.